Intravenous antiplatelet therapies (glycoprotein IIb/IIIa receptor inhibitors and cangrelor) in percutaneous coronary intervention: from pharmacology to indications for clinical use - Capodanno, Davide (Ther Adv Cardiovasc Dis, 2019)
Oral antiplatelet drugs are crucially important for patients with acute coronary syndrome or stable coronary artery disease undergoing percutaneous coronary intervention (PCI). In recent decades, several clinical trials have focused on reducing periprocedural ischemic events in patients undergoing PCI by means of more rapid platelet inhibition with the use of intravenous antiplatelet drugs. Glycoprotein IIb/IIIa receptor inhibitors (GPIs) block the final common pathway of platelet aggregation and enable potent inhibition in the peri-PCI period. In recent years, however, the use of GPIs has decreased due to bleeding concerns and the availability of more potent oral P2Y(12) inhibitors. Cangrelor is an intravenous P2Y(12) receptor antagonist. In a large-scale regulatory trial, cangrelor administration during PCI allowed for rapid, potent and rapidly reversible inhibition of platelet aggregation, with an anti-ischemic benefit and no increase in major bleeding. This article aims to provide an overview of general pharmacology, supporting evidence and current status of intravenous antiplatelet therapies (GPIs and cangrelor), with a focus on contemporary indications for their clinical use.